ANALISIS KETERAMPILAN KEAKSARAAN AWAL ANAK KELOMPOK A PADA PEMBELAJARAN BAHASA INGGRIS DI TK AL-AZHAR 35 SURABAYA - Aninda Tusyifa Faridatu Rohmah; Sri Setyowati; Mallevi Agustin Ningrum; Yes Matheos Lasarus Malaikosa (Institut Agama Islam Nahdlatul Ulama Tuban, 2026)
Early reading skills are a crucial literacy foundation for young children, yet they are often taught using monotonous conventional methods. This study aims to analyze the implementation of English language learning in stimulating early reading skills in Group A children (aged 4-5 years) at TK Islam Al-Azhar 35 Surabaya. This study employed a descriptive qualitative approach with a case study design. Data were collected through non-participant observation, in-depth interviews with teachers and the school principal, and documentation. The data analysis technique followed the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results indicated that the stimulation of early reading skills was implemented integratively through the